Basic Psychological Needs Satisfaction Mediates the Association between Self-Control Skills and Subjective Well-Being - Orkibi, Hod; Ronen, Tammie (Frontiers in Psychology, 2017)
Although studies have shown that self-control skills are positively linked to both personal and interpersonal outcomes in adolescent students, studies on the putative mechanisms underlying this relationship are scarce. Drawing on Self-Determination Theory and previous studies, we theorized that the association between students' self-control skills and their subjective well-being in school may be mediated by students' perceived satisfaction of their basic psychological needs for competence, relatedness, and autonomy. The sample consisted of 1576 Israeli adolescent students (54% girls) in grades 10-12 (mean age 16) enrolled in 20 schools. A mediation model was tested with structural equation modelling and a robust bootstrap method for testing indirect effects, controlling for school-level variance. The findings supported the hypothesized model and a post-hoc multi-group comparison analysis yielded gender invariance in the model. The findings suggest that both girls and boys with high self-control skills may perceive themselves as having greater needs satisfaction in school and consequently higher school-related subjective well-being. Implications for policy and practice are discussed.